TVET Reform in Federal Republic Nepal - Lamsal, Hari Prasad (Journal of Technical and Vocational Education and Training, 2021)
The Technical and Vocational Education and Training (TVET) includes two components - education and training that offers both academic and skill development. However, there is no uniform understanding among the countries on what these aspects should entail and variations can also be observed in governance and management. The Constitution of Nepal 2015 has demanded a complete restructuring of the country’s governance, including the reform of the education and TVET sector. This paper aims to shed light on the status of TVET in Nepal in the federal context and explores the management structures for the country to move forward in the changed context. Reviewing international practice, proposals are made with regard to the restructuring of the TVET. It suggests Nepali education system adopted a two-pronged strategy to facilitate the required reform in TVET sector and setup: a) reforms in existing programs and, b) structural changes.